The 1966–67 increase in solar cosmic-ray activity - Masley, A. J.; Goedeke, A. D. (Canadian Journal of Physics, 1968)
A significant increase in solar cosmic-ray activity began in early 1966. During the period from March 1966 to June 1967, 14 events were observed. This can be compared to one event in 1964 and one event in 1965. Events in 1966 occurred on 24 March, 7 July, 28 August, 2 September, and 14 September. Events in 1967 include those of 28 January, 2 February, 7 February, 13 February, 11 March, 23 March, 23 May, 28 May, and 6 June.The 2 September 1966 event, reaching a maximum of 13 dB (~10 5 /cm 2 s > 2 MeV), was the largest observed since July 1961. The 23 May 1967 event, with 11 dB, reached maximum absorption 35 hours after first observation. The 28 January 1967 event exhibits several interesting features. There is an apparent lack of a visible flare. Low-energy particles were observed for several hours before neutron monitors observed an event in excess of 15%, representing a low-energy precursor to the high-energy event. Details of these events are discussed. Parameters related to acceleration and propagation such as delay times and intensity–time profiles, effects related to other geophysical phenomena, and comparisons with satellite observations are also included. This paper is based on 30-MHz riometer observations at the Douglas Observatories located at McMurdo, Antarctica, and Shepherd Bay, N.W.T., Canada (80° geomagnetic latitude). The measured absorption is proportional to the square root of the particle intensity.